Investigation and experiment of radar systems in unmanned aerial vehicles-I - Suren, S (Nanyang Technological University, 2024)
Unmanned Aerial Vehicles (UAVs) have transformed the landscape of defence and security, emerging as crucial assets in intelligence and reconnaissance missions. Their role in achieving information dominance in contemporary warfare is increasingly significant. Synthetic Aperture Radar (SAR), a sophisticated radar technology, has expanded its presence markedly in both military strategies and research initiatives. The focus of this project is to delve into building a SAR system simulation, specifically its integration and functionality within UAV platforms. By employing MATLAB Simulink for simulation purposes, this study will evaluate SAR’s technical parameters and the efficacy of its core image processing algorithms, primarily Matched Filtering and the Range Migration Algorithm.